The truth about nature : a family's guide to 144 common myths about the great outdoors - Tornio, Stacy (FalconGuides, 2014)
"Does moss grow only on the north side of a tree? Should I always wait an hour after swimming? Do hummingbirds really migrate on the backs of other birds? Find out in The Truth About Nature by the authors of The Kids' Outdoor Adventure Book. This companion title, unlike other nature-myth titles for children, won't focus on classic mythology and folklore, but rather will be a useful compendium debunking everyday myths with which children can relate. Organized by season, these 144 nature-based fables will educate, breaking down the myth with an illustrated myth scale depicting how true the myth really is (level 1 being true and level 3 a complete myth). Each item has a takeaway at the end with hands-on ideas to encourage kids to get outside. In addition, kids will also find "Be a Scientist" activities throughout the book where they can try some experiments to bust a few myths on their own, as well as "Incredible Nature" sections highlighting some of the unbelievable yet true. The Truth About Nature will serve as a resource for kids and families for years to come, setting the record straight for many nature myths once and for all"--